Poker : the parody of capitalism - Bjerg, Ole, 1974- (Book collections on Project MUSE., 2011)
Poker is an extraordinary worldwide phenomenon with major social, cultural, and political implications, and Poker: The Parody of Capitalism investigates the game of poker as a cultural expression of significance not unlike art, literature, film, or music. Tracing the history of poker and comparing the evolution of the game to the development of capitalism, Ole Bjerg complicates prevalent notions of "casino capitalism" and correspondingly facile and simplistic comparisons of late capitalism and poker. By employing Slavoj iek's threefold distinction between imaginary-symbolic-real as a philosophical framework to analyze poker and to understand the basic strategies of the game, Bjerg explores the structural characteristics of poker in relation to other games, making a clear distinction between poker and other gambling games of pure chance such as roulette and craps. With its combination of social theory and empirical research, Poker offers an engaging exploration of a cultural trend. "Poker is a theoretically sophisticated, highly original and innovative treatment of a contemporary social phenomenon, and contributes greatly to our understanding of the nature of contemporary capitalism."--Charles Livingstone, Monash University Australia.